The implications of mass higher education. Papers read at an international conference held at the University of Lancaster, England, September 1972. [With contribs of H.(J.). Perkin, E. Ashby, H. Wasser a.o.]
Higher Education. An international journal of higher education and educational planning. Vol. 2, 1973, no 2, May. Special issue.